Konsep Perkawinan dalam Perspektif Mazhab Fiqh: Studi Komparatif atas Pandangan Fuqaha Klasik - Mauliyanti; Miftahul Huda (Al-Kindi, 2026)
Marriage is a fundamental institution in Islam that not only functions as a legal bond between a man and a woman, but also as a means of maintaining social order and realizing the objectives of sharia (maqāṣid al-syarī‘ah). In the Islamic fiqh tradition, marriage law has been studied in depth by classical jurists from various schools of thought, resulting in a variety of legal views based on the istinbāṭ methodology used. This study aims to analyze the views of classical jurists from the Hanafi, Maliki, Shafi‘i, and Hanbali schools of thought regarding marriage law in Islam, identify similarities and differences in views between schools regarding fundamental aspects of marriage, and examine the methodological basis behind these differences. The research method used is normative legal research with a conceptual and comparative approach, through a review of classical fiqh literature and works on ushul fiqh. The results of this study indicate that despite similarities in views between schools of thought regarding the objectives and basic principles of marriage, there are significant differences in the pillars and requirements of marriage, the role of guardians, witnesses, and the legal consequences of marriage, influenced by differences in legal sources, methods of reasoning, and the use of qiyās, istihsān, and maslahah. This study confirms that the differing views of classical jurists constitute a rich treasure trove of Islamic law relevant to serve as a reference in the development of contemporary Islamic marriage law.